Performance analysis of EDFA for SCM/WDM radio over fiber communication link - Arief Marwanto, 1975-, author; Sevia Mahdaliza Idrus Sutan Nameh, author; Abu Sahmah Mohd. Supa'at, author (Skudai : Universiti Teknologi Malaysia)
PRZSL